Forest governance and institutional structure: an ignored dimension of community based forest management in the Philippines - Dahal, G.R.; Capistrano, D. (2006)
This paper identifies strategic weaknesses in the devolution policy process in forest management and analyses the reasons behind them. Further, it establishes the relationship of devolution policy outcomes with governance and institutional structures. The field research was undertaken in the Philippines, taking six cases of community based forest management (CBFM) sites in the province of Nueva Vizcaya and Quirino and employing a qualitative technique for data collection and interpretation. The study demonstrates that the devolution policy process has two major interrelated strategic weaknesses: one is inadequate policy articulation and the other is a set of differences between policy and the complex reality of implementation. Drawing upon this analysis of strategic weaknesses in the devolution policy process in the Philippines the paper argues that the level of success of policy outcomes is dependent on the interrelation between the levels of devolution with clear policy articulation on the one hand and quality of governance and institutional structures on the other.